3-[(N-Methylanilino)methyl]-5-(thiophen-2-yl)-1,3,4-oxadiazole-2(3H)-thione - El-Emam, Ali A. (International Union of Crystallography, 2012)
In the title compound, C(14)H(13)N(3)OS(2), the thiophene ring is disordered over two orientations by ca 180° about the C—C bond axis linking the ring to the rest of the molecule, with a site-occupancy ratio of 0.651 (5):0.349 (5). The central 1,3,4-oxadiazole-2(3H)-thione ring forms dihedral angles of 9.2 (5), 4.6 (11) and 47.70 (7)° with the major and minor parts of the disordered thiophene ring and the terminal phenyl ring, respectively. In the crystal, no significant intermolecular hydrogen bonds are observed. The crystal packing is stabilized by π–π interactions [centroid–centroid distance = 3.589 (2) Å].